# Find p(0), p(1) and p (2) for each of the following polynomials:

(i) p(y) = y^{2} - y + 1 (ii) p(t) = 2 + t + 2t^{2} - t^{3}^{ }iii) p(x) = x^{3 }

iv) p(x) = (x - 1)(x + 1)

**Solution:**

To find the values p(0), p(1), and p (2) for each of the following polynomials we need to substitute the value of y as 0, 1, and 2 respectively in the given polynomial.

Let's look into the steps below.

**(i)** p(y) = y^{2} - y + 1

p(0) = (0)^{2} - (0) + 1 = 1

p(1) = (1)^{2} - (1) + 1 = 1

p(2) = (2)^{2} - 2 + 1 = 3

**(ii)** p(t) = 2 + t + 2t^{2} - t^{3}

p(0) = 2 + 0 + 2(0)^{2} - (0)^{3}

= 2 + 0 + 0 - 0 = 2

p(1) = 2 + 1 + 2(1)^{2} - (1)^{3}

= 2 + 1 + 2 - 1 = 4

p(2) = 2 + 2 + 2(2)^{2} - (2)^{3}

= 2 + 2 + 8 - 8 = 4

**(iii)** p(x) = x^{3}

p(0) = (0)^{3} = 0

p(1) = (1)^{3} = 1

p(2) = (2)^{3} = 8

**(iv)** p(x) = (x - 1)(x + 1)

p(x) = x^{2} - 1 [Using the identity (a + b)(a - b) = a^{2} - b^{2}]

p(0) = (0)^{2} - 1 = -1

p(1) = (1)^{2} - 1 = 0

p(2) = (2)^{2} - 1 = 3

**☛ Check: **NCERT Solutions Class 9 Maths Chapter 2

**Video Solution:**

## Find p(0), p(1) and p(2) for each of the following polynomials: (i) p(y) = y² - y + 1 (ii) p(t) = 2 + t + 2t² - t³^{ }(iii) p(x) = x³^{ }(iv) p(x) = (x - 1)(x + 1)

NCERT Solutions Class 9 Maths Chapter 2 Exercise 2.2 Question 2

**Summary:**

The values of p(0), p(1), p(2) for each of the following polynomials p(y) = y^{2}− y + 1, p(t) = 2 + t + 2t^{2 }− t^{3}, p(x) = x^{3}, and p(x) = (x−1) (x+1) are {1, 1, 3}, {2, 4, 4}, {0, 1, 8}, and {-1, 0, 3} respectively.

**☛ Related Questions:**

- Find the value of the polynomial 5x - 4x² + 3 ati) x = 0ii) x = -1iii) x = 2
- Verify whether the following are zeroes of the polynomial, indicated against them.(i) p(x) = 3x + 1, x = -(1/3)(ii) p(x) = 5x - π , x = 4/5(iii) p(x) = x2 - 1, x = 1, -1(iv) p(x) = (x + 1)(x - 2), x = -1, 2(v) p(x) = x2 , x = 0(vi) p(x) = lx + m, x = -(m/l)(vii) p(x) = 3x2 - 1, x = -(1/√3), 2/√3(viii) p(x) = 2x + 1, x = 1/2
- Find the zero of the polynomials in each of the following cases:(i) p(x) = x + 5(ii) p(x) = x - 5(iii) p(x) = 2x + 5(iv) p(x) = 3x - 2(v) p(x) = 3x(vi) p(x) = ax, a ≠ 0(vii) p(x) = cx + d, c ≠ 0, c, d are real numbers.

visual curriculum